STATE OF LABOR LEGISLATION AND ITS ASSESSMENT IN UKRAINE - Калюга, Александр; Калюга, Евгения (SWorldJournal, 2021)
Radical change of society in connection with socio-economic transformations is to some extent related to labor relations. The need to modernize labor legislation is due to radical changes in the entire system of social relations occurring in Ukraine in c